DAMPAK PENERAPAN E-COMMERCE AMAZON TERHADAP PENINGKATAN EKSPOR UMKM DI INDONESIA - Nayilla Putri Ramadhanti; Nurul Afifah; Tasya Salsabila Kautsar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract. The purpose of this study is to see how the implementation of e-commerce through the Amazon platform impacts the growth of MSME exports in Indonesia. Contributing more than 61% of GDP and 97% of employment, MSMEs are pillars of the national economy. Despite their great potential, MSMEs often face obstacles such as limited access to international markets, lack of understanding of digital technology, and difficulty meeting global standards. Through Amazon, MSMEs gain direct access to millions of global consumers, efficient logistics infrastructure, and analytical tools to understand market behavior. This research is qualitative in nature and uses a descriptive-analytical approach that relies on literature studies from various sources. The results show that Amazon is able to increase the visibility of MSME products and facilitate international market expansion more effectively than conventional methods. However, significant challenges remain, including high selling costs, intense global competition, and low digital readiness of MSMEs. In addition, government support in the form of training, access to funding, and supportive regulations are necessary for MSMEs to compete in the global market. With the optimization of strategies and collaboration between MSMEs, the government, and Amazon, this platform has the potential to become a catalyst for increasing exports of Indonesian MSMEs in the digital era. Keywords: e-commerce, Amazon, exports, MSMEs, and Indonesia Abstrak. Tujuan penelitian ini adalah untuk melihat bagaimana penerapan e-commerce melalui platform Amazon berdampak pada pertumbuhan ekspor UMKM di Indonesia. Dengan kontribusi lebih dari 61% PDB dan 97% lapangan kerja, UMKM adalah pilar ekonomi nasional. Meskipun memiliki potensi besar, UMKM sering kali menghadapi kendala seperti keterbatasan akses pasar internasional, kurangnya pemahaman teknologi digital, serta kesulitan memenuhi standar global. Melalui Amazon, UMKM mendapatkan akses langsung ke jutaan konsumen global, infrastruktur logistik yang efisien, dan alat analitik untuk memahami perilaku pasar. Penelitian ini bersifat kualitatif dan menggunakan pendekatan deskriptif-analitis yang bergantung pada studi literatur dari berbagai sumber. Hasil penelitian menunjukkan bahwa Amazon mampu meningkatkan visibilitas produk UMKM dan memfasilitasi ekspansi pasar internasional dengan lebih efektif dibandingkan metode konvensional. Namun, tantangan signifikan tetap ada, termasuk biaya penjualan yang tinggi, ketatnya persaingan global, dan rendahnya kesiapan digital UMKM. Selain itu, dukungan pemerintah berupa pelatihan, akses pendanaan, dan regulasi yang mendukung sangat diperlukan agar UMKM dapat bersaing di pasar global. Dengan optimalisasi strategi dan kolaborasi antara UMKM, pemerintah, dan Amazon, platform ini memiliki potensi menjadi katalisator peningkatan ekspor UMKM Indonesia di era digital. Kata kunci : e-commerce, Amazon, ekspor, UMKM, dan Indonesia.